Fabrication of CuSn functionally gradient electrode and its application in EDM for processing micro-groove - Bin Xu; Weitong Liu; Shutian Zhang; Likuan Zhu; Qingyong Zhou; Xiaoyu Wu (Journal of Materials Research and Technology, 2025)
In electrical discharge machining (EDM), different area of the tool electrode had different wear rate when it prepared by the different materials. Based on this characteristic, this paper used Sn-coated Cu foils to fabricated the CuSn functional gradient electrode (CuSn-FG electrode). Through electroplating technology, we electroplated Sn foil on both sides of the Cu foil and the Sn-coated Cu foils were obtained. By placing the Sn-coated Cu foils in the vacuum furnace for heat treatment, the Sn element diffused into the interior of the Cu foil and the CuSn-FG electrodes were fabricated. Using tungsten cobalt cemented carbide (YG8) as workpiece, the CuSn-FG electrodes were applied in EDM to machine micro-groove. The Sn element cannot be uniformly distributed inside the CuSn-FG electrode, causing different resistivity in different regions of the CuSn-FG electrode. Consequently, the different regions in CuSn-FG electrode had different EDM wear, which can be used to machine micro-groove. In this study, the effect of heat treatment parameters on the fabrication of CuSn-FG electrode and its EDM performance were investigated. Based on the above research, a mathematical model between the cross-sectional profile of micro-groove and CuSn-FG electrode was established based on the BiDoseResp model. This mathematical mode was used to predict the cross-sectional profiles of the micro-grooves fabricated by EDM of CuSn-FG electrodes heat-treated at different temperatures. Analyzing the prediction results and the experimental results, we found that the relative error of the mathematical model was less than 5 %, indicating the accuracy of the mathematical model.